An Overview Of The Quality Of Nursing Services In Regional Public Hospital Liun Kendage Tahuna - Gracia Christy Tooy; Chatrina Maria Agustina Bajak (UIMA Press, 2021)
Introduction: Nursing services bring affect to the image of a hospital in the eyes of the public, which then demands the professionalism of nurses in providing and regulating nursing care activities. Facts indicate a serious problem in the quality of nursing services in Indonesia. data obtained in the field stated that 43% of the public expressed dissatisfaction with the nursing services organized by the health service. Objective: The purpose of the study to identify the quality picture of nursing services is reviewed from the dimensions of reliability, empathy, responsiveness, assurance, and physical appearance (tangibility) of nurses at Liun Kendage Tahuna Regional Hospital in Sangihe Islands Regency. Method: This research is a descriptive research using analytical survey method. The population of this research is all outpatients and inpatients at Liun kendage Tahuna Hospital. The sampling method used in this research is purposive sampling method with a total of 97 respondents. Results: In this study, most respondents belonged to the productive age category of 25-54 years (55.7%) and the highest education achieved only to high school (35.1%). The results showed excellent reability dimension (99%), excellent empathy dimension (90.7%), excellent responsiveness dimension (93.8%), excellent assurance dimension (93.8%) as well as tangability dimensions that fall into the excellent category (80.4%). Conclusion: The quality of nursing services at Liun Kendage Tahuna Hospital belongs to the excellent category. It is necessary to do some activities such as the following; routine evaluation activities, motivational activities to nurses to always look neat and clean and activities to maintain the cleanliness of existing health facilities..